Plant-Derived Catechols Are Substrates of TonB-Dependent Transporters and Sensitize Pseudomonas aeruginosa to Siderophore-Drug Conjugates - Alexandre Luscher; Véronique Gasser; Dirk Bumann; Gaëtan L. A. Mislin; Isabelle J. Schalk; Thilo Köhler (mBio, 2022)
ABSTRACT Pseudomonas aeruginosa is an opportunistic pathogen responsible for acute and chronic infections in immunocompromised hosts. This organism is known to compete efficiently against coinfecting microorganisms, due in part to the secretion of antimicrobial molecules and the synthesis of siderophore molecules with high affinity for iron. P. aeruginosa possess a large repertoire of TonB-dependent transporters for the uptake of its own, as well as xenosiderophores released from other bacteria or fungi. Here, we show that P. aeruginosa is also capable of utilizing plant-derived polyphenols as an iron source. We found that exclusively plant-derived phenols containing a catechol group (i.e., chlorogenic acid, caffeic acid, quercetin, luteolin) induce the expression of the TonB-dependent transporters PiuA or PirA. This induction requires the two-component system PirR-PirS. Chlorogenic acid in its Fe(III)-loaded form was actively transported by PiuA and PirA and supported growth under iron-limiting conditions. Coincidentally, PiuA and PirA are also the main TonB transporters for the recently approved siderophore-drug conjugate cefiderocol. Surprisingly, quercetin supplementation increased the susceptibility of P. aeruginosa to siderophore-drug conjugates, due to induction of piuA and pirA expression mediated by the PirR-PirS two-component system. These findings suggest a potential novel therapeutic application for these biologically active dietary polyphenols. IMPORTANCE Iron is an essential element for living organisms. Most bacteria synthesize species-specific iron chelators, called siderophores, able to capture iron from their host or the environment. Pseudomonas aeruginosa, an opportunistic pathogen, produces two endogenous siderophores but is able to acquire iron also via xenosiderophores, produced by other bacteria or fungi, using a set of conserved TonB transporters. Here, we show that P. aeruginosa is also able to use plant metabolites, like quercetin and chlorogenic acid, as siderophores. These metabolites possess an iron-chelating catechol group and are recognized and transported by the TonB transporters PirA and PiuA. Since these transporters also promote the specific uptake of siderophore-drug conjugates, P. aeruginosa exposed to these plant catechols becomes hypersusceptible to this novel class of antibiotics. This unexpected finding suggests a potential therapeutic application for quercetin and chlorogenic acid, which were mainly investigated for their antioxidant and anti-inflammatory properties.